2017
DOI: 10.3171/2017.2.spine16861
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for preoperative deep venous thrombosis in 314 consecutive patients undergoing surgery for spinal metastasis

Abstract: OBJECTIVEThe authors of this study aimed to identify the incidence of and risk factors for preoperative deep venous thrombosis (DVT) in patients undergoing surgical treatment for spinal metastases.METHODSUnivariate analysis of patient age, sex, ethnicity, laboratory values, comorbidities, preoperative ambulatory status, histopathological classification, spinal level, and surgical details was performed. Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…have demonstrated that non-ambulatory status is an independent risk factor for positive finding on preoperative DVT screening. 24% of non-ambulatory patients suffer from DVT, and this incidence of DVT is 4 times higher than that of ambulatory patient population ( 27 ). These conclusions indicate that early gait training is important to prevent VTE, although it may take a long time for the muscle strength to reach the level required for walking.…”
Section: Discussionmentioning
confidence: 99%
“…have demonstrated that non-ambulatory status is an independent risk factor for positive finding on preoperative DVT screening. 24% of non-ambulatory patients suffer from DVT, and this incidence of DVT is 4 times higher than that of ambulatory patient population ( 27 ). These conclusions indicate that early gait training is important to prevent VTE, although it may take a long time for the muscle strength to reach the level required for walking.…”
Section: Discussionmentioning
confidence: 99%
“…ICU clinicians were suggested to pay more attention to these risk factors during the prevention and treatment of VTE. [2123]…”
Section: Discussionmentioning
confidence: 99%
“…5 Many orthopedic surgery subspecialties have defined standards for VTE prophylaxis, however, there is no consensus on standard prophylaxis in spine surgery. [6][7][8] There is a wide range of prophylaxis mechanism currently used that can be divided into mechanical and pharmacologic categories. Mechanical prophylaxis can include external compression devices, inferior Vena Cava filters, or early mobilization following surgery.…”
Section: Introductionmentioning
confidence: 99%